Internal Audit Outsourcing and Sustainable Audit Success: An Empirical Investigation of Listed Companies in The Stock Exchange of Thailand - Wangcharoendate, Suwan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
Internal audit outsourcing has been the focus of much attention in recent years. This study is to investigate the effects of internal audit outsourcing on sustainable audit success via the mediating influences of operational effectiveness, which include financial reporting reliability, audit effectiveness, and corporate governance achievement. In addition, professional learning is the moderating variable of the relationship between internal audit outsourcing and operation effectiveness of Listed Companies in The Stock Exchange of Thailand (SET), according to data from a survey administered to internal audit directors substituting at The Stock Exchange of Thailand.Based on data from 136 persons,the results from the Ordinary Least Squares (OLS) regression analysis employed to examine all hypotheses indicated that most of the variables from the outsourced internal audit were positively significant, and related to factors relevant to financial reporting reliability, audit effectiveness, corporate governance achievement and sustainable audit success. Specifically, evidence was found that financial reporting reliability had a positive significance to audit effectiveness, and audit effectiveness also had a positive significance to the corporate governance achievement. Additionally, professional learning is positively related to internal audit outsourcing, but interaction showed a negative relationship to efficiency risk management.These results suggest that internal audit outsourcing is an expanding business opportunity for professional accountants. This study contributes to our understanding of internal audit services and it allows companies to set a benchmark in internal auditing. However, future research is needed to collect in-depth data so as to reflect more accurately the actual concept of internal audit outsourcing.